Regional performance in the Research, Innovation and Competitiveness Priorities of the Energy Union - Georgakaki, Aliki; Jiménez-Navarro, Juan Pablo; Pasimeni, Francesco; Fiorini, Alessandro; Marmier, Alain; Asensio, José-Miguel (My University, 2018)
The current political and economic challenges faced by the European Union and its Member States call even more for evidence-informed policies. They also require tailor-made policies, developed using highly sophis- ticated analyses based not only on country-level data, but rather on regional and sub-regional knowledge. National averages, in particular, bear the risk to present a misleading picture in countries with significant disparities between different regions and areas. Looking only at national averages can also limit and delay understanding of the differences between regions and cities – identifying leaders and laggards –, as well as prevent the identification of emerging trends in certain socio-economic indicators. Only a detailed analysis of data at regional and local level can bring these insights. The Joint Research Centre (JRC) of the European Commission has developed the Socio-economic regional microscope. It is a new series of short periodical publications which aims to open-up new areas of analysis, and present the stories which can only be told using regional socio-economic data. Each report presents EU socio-economic indicators according to a data storytelling principle, using a combination of three key elements: data, visuals (maps), and narrative. Each indicator will therefore be represented through maps at regional level (NUTS2), and in some cases even at the NUTS3 and local level. The Socio-economic regional microscope will also show the breadth of the JRC regional analysis in a wide range of research areas: culture, economics, education, energy, healthcare, research and innovation, tourism, etc. The reports, data and maps are also available on the Territorial Dashboard website of the JRC Knowledge Centre for Territorial Policies, in the Thematic Analyses section: http://urban.jrc.ec.europa.eu/t-board/index. html#/thematic-analyses.
Política de acceso abierto del editor: https://data.jrc.ec.europa.eu/licence/com_reuse
Keywords: Energía; Regional innovation; NUTS2 innovation; Energy patents